Treatment of A3.2 and A2 traumatic thoracolumbar spine compression fractures using vertebral body stenting: a 63-patient series. (15th March 2022) - Salle, Henri; Tran, Gia van; Faure, Patrick; Mounayer, Charbel; Rouchaud, Aymeric; Salle, Laurence; Caire, François
Abstract : Background: Percutaneous treatments for spinal injury are underused by neuroradiologists and spine surgeons, mainly owing to a lack of data on indications. Objective: To assess the safety and efficacy of vertebral body stenting (VBS) for post-traumatic A3.2 and A2 fractures (Magerl classification) and determine the factors that influence the improvements. Methods: We retrospectively reviewed patients who underwent VBS to treat a single traumatic thoracolumbar fracture from 2010 to 2019. Kyphosis, loss of vertebral body height (VBH), and clinical and functional outcomes (including the Visual Analog Scale pain score and Oswestry Disability Index) were assessed. We examined the overall effects of VBH in all patients by constructing a linear statistical model and evaluated whether the efficacy was dependent on the characteristics of the patients or fractures. Results: We included 63 patients comprising 44 A3.2 and 19 A2 fractures. No patient had worsening neurological symptoms or wound infection. The average rates of change were 67.1% (95% CI 59.1% to 75%) for kyphosis and 88.5% (95% CI 85.6% to 91.3%) for VBH (both p<0.0001). After 1 year, the VBS treatment was more effective for kyphosis in younger patients and at the L1 level, and for VBH in younger patients and cases of Magerl A3.2 fracture. Conclusions: This large reported series on VBS validates this surgical treatment. All patients had improved kyphosis and restored VBH. We recommend using VBS rather than open surgery for A3.2 and A2 fractures at the thoracolumbar junction and in young patients.